Neuroimaging and psychophysiological investigation of the link between anxiety, enhanced affective reactivity and interoception in people with joint hypermobility - Mallorquí-Bagué, Núria; Garfinkel, Sarah N.; Engels, Miriam; Eccles, Jessica A.; Pailhez, Guillem; Bulbena, Antonio; Critchley, Hugo D. (Frontiers in Psychology, 2014)
Objective: Anxiety is associated with increased physiological reactivity and also increased ‘interoceptive’ sensitivity to such changes in internal bodily arousal. Joint hypermobility, an expression of a common variation in the connective tissue protein collagen, is increasingly recognized as a risk factor to anxiety and related disorders. This study explored the link between anxiety, interoceptive sensitivity and hypermobility in a sub-clinical population using neuroimaging and psychophysiological evaluation. Methods: Thirty-six healthy volunteers undertook interoceptive sensitivity tests, a clinical examination for hypermobility and completed validated questionnaire measures of state, anxiety and body awareness tendency. Nineteen participants also performed an emotional processing paradigm during functional neuroimaging. Results: We confirmed a significant relationship between state anxiety score and joint hypermobility. Interoceptive sensitivity mediated the relationship between state anxiety and hypermobility. Hypermobile, compared to non-hypermobile, participants displayed heightened neural reactivity to sad and angry scenes within brain regions implicated in anxious feeling states, notably insular cortex. Conclusions: Our findings highlight the dependence of anxiety state on bodily context, and increase our understanding of the mechanisms through which vulnerability to anxiety disorders arises in people bearing a common variant of collagen.